Let my people go! [videorecording (DVD)] - Buch, Mikael, 1983-; Maura, Carmen, 1945-; Maury, Nicolas; Casar, Amira; Stévenin, Jean-François; Sibony, Clément, 1976- (Zeitgeist Films, 2012)
A sweet and hilarious fusion of gay romantic comedy, Jewish family drama, Let My People Go!; follows the travails and daydreams of the lovelorn Reuben, a French-Jewish guy living in Finland with his gorgeous Nordic companion. But just before Passover, a series of mishaps and quarrels exile the heartbroken Reuben back to Paris and his zany family. Let My People Go!; both celebrates and upends Jewish and gay stereotypes with wit, gusto and style to spare.